2022
DOI: 10.1088/1741-4326/ac71b6
|View full text |Cite
|
Sign up to set email alerts
|

Solenoid-free current drive via ECRH in EXL-50 spherical torus plasmas

Abstract: As a new spherical tokamak (ST) designed to simplify engineering requirements of a possible future fusion power source, the EXL-50 experiment features a low aspect ratio (A) vacuum vessel (VV), encircling a central post assembly containing the toroidal field coil conductors without a central solenoid. Multiple electron cyclotron resonance heating (ECRH) resonances are located within the VV to improve current drive effectiveness. Copious energetic electrons are produced and measured with hard X-ray detectors, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…further supports this finding, demonstrating that the current carried by energetic electrons plays a dominant role in shaping the closed magnetic flux surface (Shi et al. 2022; Wang et al. 2022).…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“…further supports this finding, demonstrating that the current carried by energetic electrons plays a dominant role in shaping the closed magnetic flux surface (Shi et al. 2022; Wang et al. 2022).…”
Section: Introductionsupporting
confidence: 53%
“…The EXL-50 uses two sets of 28 GHz ECW systems (O-mode) to heat the plasma and drive plasma current (Shi et al. 2022; Wang et al. 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has a major radius of 0.58 m. One of the critical experimental goals of EXL-50 tokamak is to assess the effectiveness of electron cyclotron current drive (ECCD) and electron cyclotron resonance heating (ECRH) in the absence of a center solenoid (CS) magnet. It has been demonstrated that the ECRH can achieve steady-state high-efficiency current drive and obtain the highest RF current drive record without a CS magnet [21][22][23]. Recently remarkable experiments have also shown plasma currents as high as 80-100 KA at line densities over 0.5 × 10 19 m −3 .…”
Section: Introductionmentioning
confidence: 99%